Analisis Distribusi Keramik Hias pada Beberapa Sentra Keramik di Indonesia - Fadhilah, Galuh Chisyti Nur; Rahman, Aulia Dzikri; Setiawan, Agus (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the distribution system of decorative ceramics in small and medium industry (SMI) centers in Malang, Bantul, Banjarnegara, and Bali. The method used is Secondary Data Analysis (ADS) with a quantitative descriptive approach. The results show that production volume and workforce have a significant influence on distribution generation and pull. Products are mostly exported, while domestic distribution is seasonal and limited. The main modes of transportation are light trucks and ferries. This study recommends a long-term growth strategy through strengthening the supply chain, increasing production capacity, and improving transportation efficiency